1976
DOI: 10.1017/s0022112076001171
|View full text |Cite
|
Sign up to set email alerts
|

Roll-cell instabilities in rotating laminar and trubulent channel flows

Abstract: The stability of laminar and turbulent channel flow is examined for cases where Coriolis forces are introduced by steady rotation about an axis perpendicular to the plane of mean flow. Linearized equations of motion are derived for small disturbances of the Taylor type. Conditions for marginal stability in laminar Couette and Poiseuille flow correspond, in part, to the analogous solutions of buoyancy-driven convection instabilities in heated fluid layers, and to those of Taylor instabilities in the flow betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
104
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 169 publications
(123 citation statements)
references
References 9 publications
17
104
1
Order By: Relevance
“…For the majority of this paper we describe rotation in terms of Ro; however, in §11 we use Ω , in accordance with experimental preference. Lezius & Johnston (1976) have shown that RPCF loses stability in the rotation parameter range 0 < Ro < 1, to spanwise periodic disturbances with critical wavenumber β ≈ 1.5585. The neutral curve takes the form…”
Section: Governing Equationsmentioning
confidence: 99%
“…For the majority of this paper we describe rotation in terms of Ro; however, in §11 we use Ω , in accordance with experimental preference. Lezius & Johnston (1976) have shown that RPCF loses stability in the rotation parameter range 0 < Ro < 1, to spanwise periodic disturbances with critical wavenumber β ≈ 1.5585. The neutral curve takes the form…”
Section: Governing Equationsmentioning
confidence: 99%
“…In RB flow, the condition for instability (24) found to re-stabilize channel flows, 8,24 at Ro values consistent with the vorticity criterion (24).…”
Section: Re-stabilization -mentioning
confidence: 90%
“…2b), that depends on the value of Ro, in agreement with previous results for other rotating shear flows. 7,8,9,10 The extent of the rotationally unstable region grows rapidly with rotation, and is quite large at Ro = 300 which is the strongest rotation depicted in figure Fig. 2a.…”
Section: A Modal Stability Propertiesmentioning
confidence: 98%
See 2 more Smart Citations